1996
DOI: 10.1016/0885-3924(96)00008-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and correlates of fatigue in lung cancer patients receiving radiation therapy: Implications for management

Abstract: The medical records of 50 consecutive patients receiving radiation therapy for histologically diagnosed lung cancer were retrospectively reviewed to determine the frequency of fatigue and its relationship to pain, depression, and other potentially treatable correlates. Fatigue developed in 39 of the 50 patients (78%), and was not strongly related to demographic or disease variables. Pain was experienced by 40 patients (80%), but depression was noted in the records of only six patients (12%). Onset of fatigue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
10

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 29 publications
2
45
0
10
Order By: Relevance
“…Prior research has suggested that cancer-related fatigue may develop as a result of cumulative effects of repeated chemotherapy administrations. 17 As we wished to examine the performance of the MFSI-SF in a sample of cancer patients expected to be experiencing fatigue, we chose to administer the MFSI-SF after the fourth cycle of chemotherapy. The demographic characteristics of the study participants are presented in Table 1.…”
Section: Participantsmentioning
confidence: 99%
“…Prior research has suggested that cancer-related fatigue may develop as a result of cumulative effects of repeated chemotherapy administrations. 17 As we wished to examine the performance of the MFSI-SF in a sample of cancer patients expected to be experiencing fatigue, we chose to administer the MFSI-SF after the fourth cycle of chemotherapy. The demographic characteristics of the study participants are presented in Table 1.…”
Section: Participantsmentioning
confidence: 99%
“…In addition to common adverse effects such as fatigue, many patients experience heightened emotional distress as a consequence of receiving radiotherapy. [1][2][3][4] A number of randomized clinical trials have documented the benefits of psychosocial interventions for patients undergoing radiotherapy. In one trial involving patients undergoing curative and palliative radiotherapy, patients receiving professionally administered relaxation training with guided imagery experienced significant reductions in depression and fatigue relative to a no-treatment control group.…”
Section: Introductionmentioning
confidence: 99%
“…Il existe, par contre, des dĂ©nominateurs communs au sein des dĂ©finitions actuelles, notamment les notions suivantes : la fatigue est subjective et multidimensionnelle (Aistars, 1987;Irvine, Vincent, Grayson, Bubela et Thompson, 1994;Piper, 1993;Rhodes, Watson et Hanson, 1998; Smets et coll., 1993; Winningham et coll., 1994), elle a diffĂ©rents modes d'expression (Hickok, Morrow, McDonald et Bellg, 1996;Smets, Garssen, Cull et deHaes, 1996) …”
Section: Contexteunclassified
“…Il existe, par contre, des dĂ©nominateurs communs au sein des dĂ©finitions actuelles, notamment les notions suivantes : la fatigue est subjective et multidimensionnelle (Aistars, 1987;Irvine, Vincent, Grayson, Bubela et Thompson, 1994;Piper, 1993;Rhodes, Watson et Hanson, 1998;Smets et coll., 1993;Winningham et coll., 1994), elle a diffĂ©rents modes d'expression (Hickok, Morrow, McDonald et Bellg, 1996;Smets, Garssen, Cull et deHaes, 1996), elle s'inscrit dans un continuum (Irvine et coll., CONJ ‱ 18/3/08 RCSIO ‱ 18/3/08 Jensen et Given, 1993) et enfin, elle implique un Ă©puisement Ă©nergĂ©tique (Irvine et coll., 1994;Robinson et Posner, 1985). Dans le milieu de la cancĂ©rologie, on dĂ©finit frĂ©quemment la fatigue comme Ă©tant une condition caractĂ©risĂ©e par des sentiments subjectifs de lassitude; de perte de force; d'endurance ou d'Ă©nergie qui varie en degrĂ©, en frĂ©quence et en durĂ©e et s'exprime de diffĂ©rentes maniĂšres (p. ex.…”
Section: Contexteunclassified
See 1 more Smart Citation